Advances in Chemical Synthesis of Fondaparinux - Yili Ding; Chamakura V. N. S. Vara Prasad; Bingyun Wang (Journal of Chemistry)
Fondaparinux (trade name Arixtra) is a safe and efficacious anticoagulant, and it is chemically related to low-molecular-weight heparins such as enoxaparin. Fondaparinux is a synthetic pentasaccharide, and its synthesis is difficult and expensive. The high cost of fondaparinux thwarts its extensive worldwide usage. Over the last two decades, several research groups and pharmaceutical companies have been interested in finding efficient and practical methods for its synthesis. The present review discusses those strategies and their pros and cons in a comparative account.